Molecular identification of five species of family Chaetomiaceae (Sordariomycetes, Ascomycota) from Iraqi soil - Mustafa Al-Dossary; SHAYMAA S. RAHEEM; MAYSOON K. ALMYAH (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Al-Dossary MA, Raheem SS, Almyah MK. 2021. Molecular identification of five species of family Chaetomiaceae (Sordariomycetes, Ascomycota) from Iraqi soil. Biodiversitas 22: 1277-1284. Five ascomycetes fungi within the family Chaetomiaceae (Sordariomycetes, Ascomycota) were isolated from Iraqi agricultural soil and identified by phenotypic characteristics and molecular analysis. Chaetomium ascotrichoides and C. subaffine are reported for the first time from the Iraqi mycobiota. Amesia atrobrunnea, Collariella bostrychodes and Ovatospora brasiliensis were previously reported from Iraq as Chaetomium atrobrunneum, C. bostrychodes, and C. brasiliense respectively. All reported species were provided with brief characterizations and photographs